1968
DOI: 10.1002/pol.1968.150060911
|View full text |Cite
|
Sign up to set email alerts
|

Base‐catalyzed hydroxymethylation of phenol by aqueous formaldehyde. Kinetics and mechanism

Abstract: The effects of formaldehyde and hemiformal equilibria on the rates of the base‐catalyzed and hydroxymethylations of phenol by aqueous formaldehyde have been treated quantitatively. A kinetic model treating all seven simultaneous, parallel, consecutive, and competing reactions, as well as the equilibria, has been shown to apply to a wide variety of the conditions and to data from other works. Concentration‐induced solvent effects on the rates and on the ortho/para‐substitution patters have been studied. The tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 16 publications
2
47
0
Order By: Relevance
“…The relative shielding for each of these positions for phenol, 2‐HMP, and 4‐HMP have been ranked based on the average ion of the alkali metal hydroxide series to give an expected relative reaction rank. The comparison rankings are generated from the relative rate constants averaged from the five separate measurements for the alkali metal hydroxides as the literature rate constants showed substantial divergence among themselves . Although the ranking from the chemical shifts (Table ) correctly predicts the average relative reaction rate of four of the five reactions based on the literature (Table ), the prediction for formaldehyde addition to position 4 of 2‐HMP, however, is substantially off.…”
Section: Discussionmentioning
confidence: 99%
“…The relative shielding for each of these positions for phenol, 2‐HMP, and 4‐HMP have been ranked based on the average ion of the alkali metal hydroxide series to give an expected relative reaction rank. The comparison rankings are generated from the relative rate constants averaged from the five separate measurements for the alkali metal hydroxides as the literature rate constants showed substantial divergence among themselves . Although the ranking from the chemical shifts (Table ) correctly predicts the average relative reaction rate of four of the five reactions based on the literature (Table ), the prediction for formaldehyde addition to position 4 of 2‐HMP, however, is substantially off.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that 2-substitution is favored over 4-substitution in the initial stages of the resol reactions and agrees with the kinetic results measured by Zavitsas et a1. 6 The relative intensity of the 570-cm-I band (Fig. 6), which is mainly contributed by 2,4-disubstituted phenol, started to appear at MW 200, showed an inflection upward at about MW 300, and increased approximately linearly thereafter.…”
Section: Resultsmentioning
confidence: 97%
“…The initial addition of formaldehyde to phenol in alkaline media could for the first time be successfully described, thanks to Zavitsas and collaborators [233]. Resol formation in further reactions is a complex process, owing to the several different aromatic reaction sites and substitution effects [234]; a total of 19 can be distinguished [235,236].…”
Section: Phenolic Resinsmentioning
confidence: 99%